1980
DOI: 10.1002/j.1537-2197.1980.tb07751.x
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Orientation, Radiation Interception, and Nocturnal Acidity Increases by the Cam Plant Agave Deserti (Agavaceae)

Abstract: Both field measurements and a computer model were used to study the interception of photosynthetically active radiation (PAR) by Agave deserti (Engelm.), a desert CAM plant with a basal rosette of massive opaque leaves. PAR interception was determined in the winter and the summer for upper and lower leaf surfaces on a plant with about 60 leaves. Total daily PAR on the leaf surfaces was approximately 10 mol m‐2 for a winter day and 20 mol m‐2 for a summer day. For a PAR of 15 mol m‐2, the nocturnal increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1
2

Year Published

1982
1982
2013
2013

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 14 publications
1
23
1
2
Order By: Relevance
“…4), which apparently surpasses other field measurements on this species (19,26) as well as on all other CAM plants, e.g. maximum uptake in the field is 0.65 mol m-2 for A. deserti (31), 0.70 mol m-2 for Opuntia inermis (24), and 0.76 mol m-2 for Opunta chlorotica (17). Furthermore, irrigated 0. ficus-indica can maintain a substantial net assimilation rate throughout the year (Fig.…”
Section: Resultsmentioning
confidence: 57%
“…4), which apparently surpasses other field measurements on this species (19,26) as well as on all other CAM plants, e.g. maximum uptake in the field is 0.65 mol m-2 for A. deserti (31), 0.70 mol m-2 for Opuntia inermis (24), and 0.76 mol m-2 for Opunta chlorotica (17). Furthermore, irrigated 0. ficus-indica can maintain a substantial net assimilation rate throughout the year (Fig.…”
Section: Resultsmentioning
confidence: 57%
“…For succulent agaves, CAM seems to be a ubiquitous trait, expressed many times in a quite rigid pattern with reduced gas exchange at Phases II and IV. For instance, it is known that species such as Agave deserti, A. fourcroydes, A. tequilana, A. angustifolia, A. lecheguilla, A. lurida, A. murpheyi, A. parryi, A. salmiana, A. scabra, A. schottii, A. shawii, A. sisalana, A. utahensis, A. vilmoriniana, A. virginica and A. weberii typically perform CAM photosynthesis under natural conditions [127][128][129][130][131]. Nevertheless, it was reported that Agave deserti is clearly able to change from CAM to C 3 photosynthesis when maintained under well-watered laboratory conditions [132].…”
Section: Cam In Agavaceaementioning
confidence: 99%
“…This is not surprising given the methodological difficulties in determining the effects of daytime PPFD2 on nighttime CO2 uptake. Recent (10)(11)(12)(13)(14)17). On the other hand, results of several studies of CAM in Tillandsia usneoides L. (Spanish moss) indicate that this epiphyte may exhibit saturation ofphysiological activity at PPFD levels substantially below full sunlight (1,6,7,9).…”
mentioning
confidence: 99%